Building Polyelectrolyte Multilayers with Calmodulin A Neutron and X-ray Reflectivity Study - Cinar, Süleyman (Langmuir : the ACS journal of surfaces and colloids, 2017)
We have studied the formation and functional properties of polyelectrolyte multilayers where calmodulin (CaM) is used as a polyanion. CaM is known to populate distinct conformational states upon binding Ca2+ and small ligand molecules. Therefore, we have also probed the effects of Ca2+ ions and trifluoperazine (TFP) as ligand molecule on the interfacial structures. Multilayers with the maximum sequence PEI-(PSS-PAH)x-CaM-PAH-CaM-PAH have been deposited on silicon wafers and characterized by X-ray and neutron reflectometry. From the analysis of all data, several remarkable conclusions can be drawn. When CaM is deposited for the second time, a much thicker sublayer is produced than in the first CaM deposition step. However, upon rinsing with PAH, very thin CaM-PAH sublayers remain. There are no indications that ligand TFP can be involved in the multilayer buildup due to strong CaM-PAH interactions. However, there is a significant increase in the multilayer thickness upon removal of Ca2+ ions from holo-CaM and an equivalent decrease in the multilayer thickness upon subsequent saturation of apo-CaM with Ca2+ ions. Presumably, CaM can still be toggled between an apo and a holo state, when it is embedded in polyelectrolyte multilayers, providing an approach to design bioresponsive interfaces